Viscosity and interfacial tension of n-heptane with dissolved carbon dioxide by surface light scattering (SLS). (January 2021) - Cui, Junwei; Bi, Shengshan; Fröba, Andreas P.; Wu, Jiangtao
Graphical abstract: Highlights: Viscosity and interfacial tension in the temperature range (298–473) K and pressure up to 5.5 MPa. Time dependence of liquid viscosity and interfacial tension. Correlations development of liquid viscosity and interfacial tension with empirical equation. Comparisons and discussions with available literature data. Abstract: The present work focus on the measurement of viscosity and interfacial tension of n -heptane ( n -C7 H16 ) with dissolved carbon dioxide (CO2 ) by the surface light scattering. The method allows an absolute determination of both properties in a contactless way. The experiments were conducted in macroscopic thermodynamic equilibrium at temperatures from (298 to 473) K and saturation pressures up to 5.5 MPa. For sample preparation of binary mixtures of n -C7 H16 with dissolved CO2 after its addition, the equilibration process could be checked to be completed by showing that viscosity and interfacial tension are independent on time. For reaching equilibrium, at least two hours were elapsed between the addition of CO2 and the start of the measurement. For both viscosity and interfacial tension, typical expanded uncertainties are 3% on a confidence level of 95%. The viscosity results were correlated with an empirical equation, where the absolute average deviation (AAD) and the maximum absolute deviation (MAD) between experiments and correlation were 1.9% and 7.2%, respectively. For the viscosity, a data comparison was hindered because of the lack of literature data. For the interfacial tension, which can also be represented by an empirical correlation and good agreement with literature can be found.